Model Pelaporan Kinerja Sosial Perbankan Syariah: Implementasi Islamic Social Reporting Index di Indonesia - Gustani Gustani (Jurnal Akuntansi dan Keuangan Islam, 2014)
One of the effort to increase the trust of shariah banks stakeholder is by reporting theinformation relating with the social performance ability in shariah view. The reportingsocial performance format in Islam view that nowdays is more developed is IslamicSocial Reporting Indexs (Indeks ISR). ISR Index is an index reveals social performance ofIslamic company which consists of revelation items based on Islamic principles. The aimof this research is to find out the rank of revelation social performance of Islamic bank inIndonesia based on ISR index. The taken population of this research is the whole IslamicCommercial Bank (BUS) in Indonesia, and the taken sample is the BUS that has published its annual report of 2009 – 2011 periods on its official website. The taken sampleis done by using purpose sample method. The analysis data is done by using contentanalysis method. The result of analysis ISR index on BUS shows that BSM is for thehighest rank of revelation social performance in 2009 – 2011 periods. As the wholebanks, the rank of revelation social performance of BUS in Indonesia in 2009 – 2011periods had continuously increased each year. As the average in the periods, the predicateof rank revelation social performance BUS in Indonesia is still less than informative.